Transformative Convergence: Exploring the Nexus of Engineering, Science and Technology in Intensive Care - Rojas-Díaz, Ever Leonardo (Archives of Case Reports, 2024)
In the last decade, convergence science has been described as the solution to problems by integrating biological sciences with the physical, mathematical and computational sciences. This concurrence opens the pitch to strengthen multidisciplinary, transdisciplinary and interdisciplinary work. This short review delves into the transformative integration of engineering, science and technology in the dynamic realm of intensive care. Unveiling recent advancements, the exploration spans the multifaceted contributions of these disciplines toward elevating patient care and optimizing healthcare systems.